2018
DOI: 10.1136/acupmed-2016-011187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture at ST36 on the Intestinal Mucosal Mechanical Barrier and Expression of Occludin in a Rat Model of Sepsis

Abstract: Electrical stimulation at ST36 in rats with sepsis can increase protein expression of occludin, reduce serum D-lactate levels and increase permeability of the intestinal barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…Zhang et al, [79] CLP, ligated the root of the cecum, perforated 3 times with no. 16 needle Zhang et al, [80] CLP, ligated the lower section of the cecum (25% from the blind side of its total length) using 4-0 silk threads, perforated once with a 19-gauge needle Zhu et al, [73] CLP, ligated the base of the cecum, below the ileocecal valve, with a 2.0-silk, perforated 2 times with no.18 needle Torres-Rosas et al, [21] (1) 6 mg/kg LPS, intraperitoneally…”
Section: Study (Years)mentioning
confidence: 99%
See 4 more Smart Citations
“…Zhang et al, [79] CLP, ligated the root of the cecum, perforated 3 times with no. 16 needle Zhang et al, [80] CLP, ligated the lower section of the cecum (25% from the blind side of its total length) using 4-0 silk threads, perforated once with a 19-gauge needle Zhu et al, [73] CLP, ligated the base of the cecum, below the ileocecal valve, with a 2.0-silk, perforated 2 times with no.18 needle Torres-Rosas et al, [21] (1) 6 mg/kg LPS, intraperitoneally…”
Section: Study (Years)mentioning
confidence: 99%
“…Only 6 studies [51,52,61,64,75,77] reported using adult animals, 16 studies [30,34,38,40,49,50,53,57,62,65,68,69,73,[78][79][80] had no statement about animals' age, and the remaining 33 studies reported the specific age of the animals.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 3 more Smart Citations